(untitled) (Fiep Bulletin - online, 2013)
Introduction: Obesity is now a major public health problem, because the heavy weight, coupled with a sedentary lifestyle, is directly related to pathological conditions that cause high morbidity and mortality. Several interventions are used to improve health and therefore the quality of life of obese patients. The VO2max is a variable that should be assessed and monitored in the obese population, because it is an important parameter associated morbidities, and the quantification of the highest oxygen uptake by an individual is due to the interaction of the respiratory, cardiovascular and muscular. Objective: To evaluate the maximal oxygen uptake of morbidly obese individuals preoperative bariatric surgery: Methods: We evaluated 14 patients between 21 and 50 years, 3 patients were male and 11 female patients. These patients already have the date marked bariatric surgery, which will happen in the next 6 months. They signed an informed consent form and the project was approved by the IRB of the institution. Individuals performing treadmill exercise test following the protocol of Balke. Results: Of 14 patients evaluated to date, the average maximal oxygen uptake was 20.3 ml/kg/min-1 found. Conclusions: we found that the obese population has compromised cardiorespiratory fitness as presents values ??of maximum oxygen consumption low when compared to the normal population.